ナンキョク オオガタ セツジョウシャ (SM100S) ノ カイハツ II. システムデザイン - 中島, 征志; ナカジマ, マサシ; 細谷, 昌之; ホソヤ, マサユキ; Nakajima, Masashi; Hosoya, Masayuki (1992)
P(論文) この報告は, 南極氷床ドーム深層掘削計画に使用するために新たに開発する南極大型雪上車のシステムデザインについて述べたものである。システムデザインした南極大型雪上車は, 観測隊員2名の居住宿泊施設を有し, 貨物を積載した2.6tの木製そり7台を5-8km/hの速度でけん引してトラバースできる全重量11500kgのキャブオーバ箱型車体の全装軌式である。平地から4000mの高地に至る地域に順応して, 運用は-60℃まで可能でさらに-90℃までの環境で保存ができる。システムデザインに当たっては, 期待される性能を分析して構造, 形状, 寸法を見積もり, 従来からの雪上車の実績から問題点を抽出して研究試験によって解明し実施した。 This paper describes the design of the systems of a newly developed snow vehicle, which will be used for the deep ice coring project at Dome Fuji, East Antarctica. This vehicle is a cab-over full-track type, in which the accommodations for two persons are prepared. The vehicle is 11500kg in gross weight and traverses at 5-8km/h pulling seven wooden type sledges each of which is 2.6t in loaded weight. The vehicle operates at low temperature down to -60℃ on the Antarctic ice sheet from the plain up to the high plateau of 4000m in altitude. In addition, the preservation of the vehicle is possible under the severe environment as cold as -90℃. In the process of the development, first we analyzed the requested performance and then estimated structure, configuration and dimensions of the vehicle. We extracted the problems from the other snow vehicles operated before in Antarctica and then solved them by means of experiments and researches to make use of the results for the design. departmental bulletin paper